A simplified prevention bundle with dual hand hygiene audit reduces early-onset ventilator-associated pneumonia in cardiovascular surgery units: An interrupted time-series analysis - Su, Kang-Cheng; Kou, Yu Ru; Lin, Fang-Chi; Wu, Chieh-Hung; Feng, Jia-Yih; Huang, Shiang-Fen; Shiung, Tao-Fen; Chung, Kwei-Chun; Tung, Yu-Hsiu; Yang, Kuang-Yao; Chang, Shi-Chuan (PLOS ONE, 2017)
Background To investigate the effect of a simplified prevention bundle with alcohol-based, dual hand hygiene (HH) audit on the incidence of early-onset ventilation-associated pneumonia (VAP). Methods This 3-year, quasi-experimental study with interrupted time-series analysis was conducted in two cardiovascular surgery intensive care units in a medical center. Unaware external HH audit (eHH) performed by non-unit-based observers was a routine task before and after bundle implementation. Based on the realistic ICU settings, we implemented a 3-component bundle, which included: a compulsory education program, a knowing internal HH audit (iHH) performed by unit-based observers, and a standardized oral care (OC) protocol with 0.1% chlorhexidine gluconate. The study periods comprised 4 phases: 12-month pre-implementation phase 1 (eHH+/education-/iHH-/OC-), 3-month run-in phase 2 (eHH+/education+/iHH+/OC+), 15-month implementation phase 3 (eHH+/education+/iHH+/OC+), and 6-month post-implementation phase 4 (eHH+/education-/iHH+/OC-). Results A total of 2553 ventilator-days were observed. VAP incidences (events/1000 ventilator days) in phase 1–4 were 39.1, 40.5, 15.9, and 20.4, respectively. VAP was significantly reduced by 59% in phase 3 (vs. phase 1, incidence rate ratio [IRR] 0.41, P = 0.002), but rebounded in phase 4. Moreover, VAP incidence was inversely correlated to compliance of OC (r2 = 0.531, P = 0.001) and eHH (r2 = 0.878, P < 0.001), but not applied for iHH, despite iHH compliance was higher than eHH compliance during phase 2 to 4. Compared to eHH, iHH provided more efficient and faster improvements for standard HH practice. The minimal compliances required for significant VAP reduction were 85% and 75% for OC and eHH (both P < 0.05, IRR 0.28 and 0.42, respectively). Conclusions This simplified prevention bundle effectively reduces early-onset VAP incidence. An unaware HH compliance correlates with VAP incidence. A knowing HH audit provides better improvement in HH practice. Accordingly, we suggest dual HH audit and consistent bundle performance does matter in quality-of-care VAP prevention.